2009
DOI: 10.1128/aac.01443-07
|View full text |Cite
|
Sign up to set email alerts
|

OPT-80 Eliminates Clostridium difficile and Is Sparing of Bacteroides Species during Treatment of C. difficile Infection

Abstract: During a 10-day treatment for Clostridium difficile infection, OPT-80 and vancomycin were comparably effective in reducing C. difficile counts. Bacteroides fragilis group counts appeared unaffected with increasing dosages of OPT-80, whereas vancomycin was markedly suppressive. Retention of components of the normal microflora might lower the risk of recurrent disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 10 publications
6
125
2
1
Order By: Relevance
“…Such an alternate strategy requires the utilization of narrow-spectrum antimicrobials. Indeed, the fact that the novel macrocycle OPT-80 eliminates C. difficile without impacting on members of the Bacteroides species (Bacteroides fragilis group) was regarded as noteworthy in a recent study (34). Culture-based techniques confirmed the narrow-spectrum nature of thuricin CD, in that it was not effective against a number of commercially important probiotic strains.…”
Section: Discussionmentioning
confidence: 88%
“…Such an alternate strategy requires the utilization of narrow-spectrum antimicrobials. Indeed, the fact that the novel macrocycle OPT-80 eliminates C. difficile without impacting on members of the Bacteroides species (Bacteroides fragilis group) was regarded as noteworthy in a recent study (34). Culture-based techniques confirmed the narrow-spectrum nature of thuricin CD, in that it was not effective against a number of commercially important probiotic strains.…”
Section: Discussionmentioning
confidence: 88%
“…33,34 It should be noted that rifaximin is not a widely accepted treatment modality and that there are concerns regarding the development of resistance to the medication. 40,41 Another antibiotic that holds promise for the treatment of RCDI is fidaxomicin (OPT-80). Studies using fidaxomicin as a treatment agent have shown equivalence to vancomycin in the treatment of primary CDI but with less alteration of the normal gut flora.…”
Section: Antibiotic Regimensmentioning
confidence: 99%
“…In recent phase 3 clinical trials in patients with C. difficile infection, fidaxomicin not only was well tolerated and achieved the primary end point of clinical cure but also demonstrated a significantly lower rate of recurrence of infection compared with vancomycin (Crook et al, 2010;Louie et al, 2009b;Miller et al, 2009). Analysis of stool samples from subjects during a phase 2 doseranging study demonstrated that fidaxomicin not only lacks activity against Gram-negative bacteria but is also sparing of Gram-positive commensals (Louie et al, 2009a;Tannock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%